Modelling and macroeconomic analysis of a Solar PV/diesel hybrid power plant - Mthwecu, Sabatha (Department of Electrical Engineering, 2015)
This research thesis covers the latest research on renewable energy globally and focuses on the solar panel and biofuels market. A full macroeconomic analysis is done on the Chinese Taipei, and this results in some parameters which then become the basis of this research. The macroeconomic parameters are then put into a tabular form and applied to India, Turkey and Australia to see how much weight the analysis can hold and if there is enough data per country on the macroeconomic parameters chosen. This research thesis conducts a shorter, custom version of a macroeconomic analysis on a South African area, and considers the national Gross Domestic Product, pollution, length of transmission lines, weather factors such as sunlight and temperature and more. Following from this, a hybrid power system is developed under these circumstances and the information is compared with past research. A very informative discussion is then had as to what the model means on a macroeconomic scale and how it performs technically. The technical solution at this point has no economic barriers. Economics can be a tool and not a financial hurdle in the face of technological advancement.